Synthesis of Hureaulite Mn5(H2O)4(PO3OH)2(PO4)2 with an Open 3D Network Structure as Electrode Material for Electrochemical Capacitors - García Guajardo, Cesar Iván; Zúñiga Martínez, Jorge Alexis; Berlanga Pérez, Roxana; López Pavón, Luis Alberto; Lucio Porto, Raúl (Molecular Diversity Preservation International, 2024)
Mn5(H2O)4(PO3OH)2(PO4)2 with an open 3D network was prepared and studied as electrode material for electrochemical capacitors. The material exhibits a tunnel structure along the c axis, characterized by a hydrogen bond network formed by water molecules bonded to MnO6 octahedra and PO3-OH tetrahedra units, the latter containing an acidic proton. Electrochemical studies were conducted on both alkaline and neutral electrolytes, revealing a profile indicative of a rapid faradaic process coupled with pseudocapacitance and electrochemical double-layer capacitance. This study proposes a mechanism that involves the interaction between the acidic proton in the tunnel structure and OH− ions from the electrolyte, which diffuse through the hydrogen bond network. The material achieved a maximum specific capacitance of 184 Fg−1 at a scan rate of 5 mVs−1, with an areal capacitance of 4600 µFcm−2 in 3M KOH. This demonstrates its potential as a high-performance electrode for energy storage applications.